2021
DOI: 10.1080/10447318.2021.1890489
|View full text |Cite
|
Sign up to set email alerts
|

Flying by Feeling: Communicating Flight Envelope Protection through Haptic Feedback

Abstract: Modern aircraft can be equipped with a flight envelope protection system: automation which modifies pilot control inputs to ensure that the aircraft remains within the allowable limits. Overruling the pilot inputs may lead to mode confusion, even when visual or auditory feedback is provided to alert pilots. We advocate using active control devices to make the flight envelope protection system tangible to the pilot. This paper presents the main findings of an evaluation of three haptic feedback designs for flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Studies where an effect of haptics been absent often communicate task-related information with discrete arbitrary signals that bear minimal resemblance to users' existing mental models. For instance, a recent study by Van Baelen et al [41] in 2021 found no performance benefit associated with the representation of departing a safe flight envelope through the presentation of a discrete saw-tooth vibrotactile signal. In the current study, this observation was echoed within participant comments on the lack of intuitiveness of the lateral proprioceptive cues relative to the distance to turn vibrotactile cue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies where an effect of haptics been absent often communicate task-related information with discrete arbitrary signals that bear minimal resemblance to users' existing mental models. For instance, a recent study by Van Baelen et al [41] in 2021 found no performance benefit associated with the representation of departing a safe flight envelope through the presentation of a discrete saw-tooth vibrotactile signal. In the current study, this observation was echoed within participant comments on the lack of intuitiveness of the lateral proprioceptive cues relative to the distance to turn vibrotactile cue.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research undertakings are also geared towards enhancing haptic feedback in fly-by-wire controls. For instance, Van Baelen et al [19] presented flight envelope protection through haptic feedback, incorporating both force and vibrations in the control stick. This system assists pilots in evading flight envelope speed and load factor threshold values, especially when there is a shift to an alternative control law.…”
Section: Previous Research Projects In Haptic Feedbackmentioning
confidence: 99%
“…For instance, Navarro et al (2007Navarro et al ( , 2010 developed and tested a haptic hybrid warning-guidance device called motor priming (MP) designed to help drivers keep their lane. The MP device generates asymmetrical movements on the steering wheel such that the amplitude in the direction of the lane center is larger than the amplitude in the direction of lane departure (see also Van Baelen et al, 2021). In a series of experiments (Navarro et al, 2007(Navarro et al, , 2010, the efficacy of the MP device was compared with a range of warning systems, consisting of an auditory warning (a rumble strip sound), symmetrical (i.e., directionless) steering wheel oscillations, lateral vibrations on the steering wheel (two vibrators were inserted in the upper part of the steering wheel, one on each side), and lateral vibrations on the seat (a set of vibrators was placed in the right and left sides of the base and back of the seat).…”
Section: Dual Route Hypothesismentioning
confidence: 99%